A brief history of topographical anatomy - Standring, Susan (J Anat, 2016)
This brief history of topographical anatomy begins with Egyptian medical papyri and the works known collectively as the Greco‐Arabian canon, the time line then moves on to the excitement of discovery that characterised the Renaissance, the increasing regulatory and legislative frameworks introduced in the 18th and 19th centuries, and ends with a consideration of the impact of technology that epitomises the period from the late 19th century to the present day. This paper is based on a lecture I gave at the Winter Meeting of the Anatomical Society in Cambridge in December 2015, when I was awarded the Anatomical Society Medal.